Frazeološko-leksikografski vidiki prevajanja angleških frazemov v slovenščino - Vrbinc, Alenka (Slovenski jezik, 2011)
The article focuses on the problem of translating phraseological units and their inclusion in bilingual dictionaries. Its findings are based on a database comprising approximately 250 phraseological units, all of them containing food and drink items. The English phraseological units were translated into Slovene and the Slovene translation equivalents were then analysed to establish similarities and differences between English and Sloveneand to study possible problems involved in the translation of phraseological units. According to the analysis, several groups of phraseological units can be established as regards their translation(s), ranging from idiomatic translation equivalents on the one hand to false friends on the other. The problem of where to include a phraseological unit ina dictionary is also mentioned, as it may be listed in a special section of the dictionary article or as a headword. At the end, some suggestions are madeas to the treatment of phraseological units in a bilingual dictionary where special attention is paid to the problem of monosemy vs. polysemy and the problem of translation equivalent in isolation vs. the translation of a phraseological unit in context.
Keywords: angleščina; English; frazeologija; phraseology; prevajanje; Slovene; slovenščina; translation